(untitled) (Journal of Global Arts Studies, 2023)
Background: Pop-Up Books play a crucial role in early childhood education, particularly in enhancing overall development through unique interactivity and visual impact. Purpose: To effectively inherit and innovate Traditional Chinese Medicine (TCM) culture, aiding in its integration into national education. Methods: Combining the distinctive presentation of pop-up books with virtual reality technology and the fundamental concepts of TCM, creating engaging and age-appropriate TCM educational materials for young children. Result: Developing pop-up books tailored to children’s cognitive abilities, incorporating TCM education into early childhood curriculums, and sparking interest in TCM culture. Conclusion: The integration of pop-up book design, virtual reality, and cultural elements supports national efforts to disseminate and preserve cultural heritage, effectively transmitting excellent national culture in early education.